Experimental Study on a Forced-Circulation Loop Thermosiphon Solar Water Heating System - Tao Zhang (International Journal of Photoenergy)
Wickless gravity loop thermosiphons (LTs) have been widely used in heat collection for distances up to several meters. This two-phase closed device, which is operating under reduced pressure, is useful in solar water heating (SWH) systems because it could address the freezing problem during winter. Compared to the normal type, forced-circulation wickless LTs have significant advantages in the long-distance heat transfer and installation freedom of condensation section. In this study, a pump-forced wickless LT-SWH system with a remolded flat-plate solar collector was put forward. Solar collector acted as the evaporation section of the wickless LT, while the spiral heat exchanger in the water tank acted as the condensation section. R600a was employed as the working fluid, and long-term outdoor experiments were carried out. Results show that the instantaneous and daily average photothermal efficiency of the proposed system can reach 69.54% and 58.22%, respectively. Temperature differences between the top and bottom and the middle and bottom of the evaporation section of the wickless LT were small, and it usually ranged between 1.1 and 3.9°C. Linear fittings of the collector and system overall performance of the pump-forced wickless LT-SWH system demonstrate the promising potential application of the system.